A Network-based Approach to the Repairman Queuing Problem - Newton, James A. (Florida Technological University, 1975)
Florida Technological University College of Engineering Thesis === M.S. === Masters; === Engineering === Engineering === 70 p. === v., 70 l. illus. 29 cm.